Three-dimensional elastoplastic damage concrete model by dissipation-based arc-length method. Issue 12 (December 2016) - Ma, Cheng; Chen, Wei-zhen
This article presents a three-dimensional isotropic elastoplastic damage model for concrete structures. The plasticity of concrete is described by a nonassociated flow rule, using a three-parameter yield function as well as a modified Drucker–Prager-type potential. The damage of concrete is seen as a contribution work of tensile and compressive damage, with the evolution histories driven by the internal tensile and compressive variables, respectively. The iterative solution of plasticity and damage is carried out according to the concept of operator split, where a return-mapping algorithm as well as a substepping strategy is used. The consistent tangent stiffness considering the recursive relationship among substeps is derived. For the solution of global iteration, a dissipation-based arc-length method is employed. Good agreements are found in comparisons between numerical results and experimental data on both elementary and structural levels. Furthermore, the sensitivities of parameters that control strain softening are investigated.